Biochemical Traits in the Flower Lifetime of a Mexican Mistletoe Parasitizing Mesquite Biomass - Quintana-Rodríguez, Elizabeth; Ramírez-Rodríguez, Alan Gamaliel; Ramírez-Chávez, Enrique; Molina-Torres, Jorge; Camacho-Coronel, Xicotencatl; Esparza-Claudio, José; Heil, Martin; Orona-Tamayo, Domancar (Frontiers in Plant Science, 2018)
Psittacanthus calyculatus is a hemiparasitic plant that infects a wide range of trees. Mainly the biology reproduction of this mistletoe lies in bright colored flower development. Furthermore, it uses the nectar secretion as the only reward to engage different flower visitors. We investigated the physiological mechanisms of the flower phenology per hour and per day to analyze the spatial-temporal patterns of the nectar secretion, Cell Wall Invertase Activity (key enzyme in the quality of nectar), nectar chemistry, volatile organic compounds (VOCs) emission, synthesis of carotenoids and frequency of floral visitors. Flowers lasted four days, total nectar was loaded just before the anthesis and the secretion was maintained over day 1 and 2, decreased on day three and stopped on day 4. The diurnal nectar secretion dynamic per hour on day one and two showed similar patterns with high production on the morning and a decrease in the afternoon, the secretion decline on day 3 and ceased on day 4. On the other hand, CWIN activity per day was less before the anthesis and increased on day 1 and 2, this enzymatic activity decreased on the old flower phenology. Moreover, diurnal CWIN activities showed different patterns in the morning, noon and lastly in the afternoon. Nectar chemistry varied significantly throughout of the flower lifetime, sucrose decreased along the flower phenology increasing glucose and fructose. Amino acids showed the prevalence of proline and Oxo-proline, both increased on the day 1 and diminished in subsequent old flower stages. The spatial VOCs emission showed the presence of 11 compounds being -ocimene the main volatile; its release increased on day 1 and remained constant in the flower lifetime. Lutein, lycopene and -carotene were concentrated in old stages of the flowers. In field, the most frequent flower visitors were the hummingbirds that usually foraging in all phenologic flower stage and their foraging events decreased with the phenological flower lifetimes. The results showed that these traits presented by P. calyculatus flowers are able to engage and manipulate the behavior of flower visitors and contribute to the reproduction of the parasitic plant.